Retinoblastoma metastasis: A Study at Tertiary care center in South India - Namrata N Rajakumar (Tropical Journal of Pathology and Microbiology, 2024)
Objective:Retinoblastoma is the most common primary ocular malignancy in children. Bone marrow involvement by solid tumor implicates advanced disease and bad prognosis.Bone marrow aspiration and biopsy , performed routinely for staging  for  small round cell tumors and  unexplained cytopenia in other solid tumors .It is important to rule out bone marrow involvement before planning for  any definitive ,curative treatment. Materials and Methods: This was a retrospective observational study of bone marrow involvement by , Small round cell tumors  / solid tumors and their  hematological manifestation, especially the Retinoblastomas. Results: Evaluation of  Bone marrow evaluation during past 7 years , in  solid malignancies,revealed Out of 772, 342 were pediatric cases and 430 were adult cases. Bone marrow was involved in 82 patients. In children, bone marrow involvement was present in 42 cases, and in adults, bone marrow involvement was  diagnosed in  40 cases. Neuroblastoma  was the most common malignancy, which involved the bone marrow in pediatric cases, followed Ewing’s sarcoma& retinoblastoma, Out of 16 cases  there were 6 cases of Retinoblastoma involving marrow   Conclusion:  small round blue cell tumors are the major cause of bone marrow involvement in pediatric, Retinoblastoma  metastasis is less common in advanced countries, however  not so rare in developing countries  A diligent and exhaustive search for metastatic cells in Bonemarrow helps in treatmrent and prognosis   ,Use of immunohistochemistry markers on bone marrow biopsies  results in higher detection rate,also aids in picking very few neoplastic cells ,thereby  helps in  detecting  early metastasis. RB treatment is to save the patients life,salvage of the eye and vision are secondary goals,needs multidisciplinary team approach